2007
DOI: 10.1161/circresaha.107.164178
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Demethylase, Jmjd1a, Interacts With the Myocardin Factors to Regulate SMC Differentiation Marker Gene Expression

Abstract: Abstract-We and others have previously shown that the myocardin transcription factors play critical roles in the regulation of smooth muscle cell (SMC) differentiation marker gene expression. In a yeast 2-hybrid screen for proteins that interact with myocardin-related transcription factor-A (MRTF-A), we identified the histone 3 lysine 9 (H3K9)-specific demethylase, Jmjd1a. GST pull-down assays demonstrated that Jmjd1a bound all 3 myocardin family members, and further mapping studies showed that the jumonjiC do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 63 publications
7
71
0
Order By: Relevance
“…Consistent with these data, KDM3B expression induces leukemic transformation by inhibiting leukemia cell differentiation and is upregulated in blood cells obtained from certain types of leukemia patients [82].…”
Section: Kdm3 Cluster (Jmjd1 Subfamily)supporting
confidence: 77%
See 1 more Smart Citation
“…Consistent with these data, KDM3B expression induces leukemic transformation by inhibiting leukemia cell differentiation and is upregulated in blood cells obtained from certain types of leukemia patients [82].…”
Section: Kdm3 Cluster (Jmjd1 Subfamily)supporting
confidence: 77%
“…The myocardin transcription factor interacts with KDM3A and recruits it to SMC-specific gene promoters. KDM3A subsequently demethylates H3K9me3 from these genomic regions and regulates their TGFß-mediated activation [82].…”
Section: Kdm3 Cluster (Jmjd1 Subfamily)mentioning
confidence: 99%
“…Our previous study has found that MRTF-A can drive the transcription of adhesion molecules in vascular endothelial cells by directly interacting with the p65 subunit of NF-kB (Fang et al, 2011). The ability of MRTF-A to steer transcriptional events is derived in part from its extensive crosstalk with the epigenetic machinery, including histone modifying enzymes and chromatin remodeling proteins (Hanna et al, 2009;Lockman et al, 2007;Yang et al, 2013;Zhang et al, 2007;Zhou et al, 2009). Building on these findings, we hypothesized that MRTF-A could fine-tune LPS-induced NFkB-dependent pro-inflammatory transcription in macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Histone demethylase LSD1 plays a key role in muscle differentiation by controlling epigenetic marks in the myogenin and myosin heavy chain gene promoters (21). Jmjd1a demethylates H3K9 in the myosin heavy chain gene promoter and enhances muscle differentiation by interacting with myocardin factors (22).…”
mentioning
confidence: 99%